Overcoming the barriers to dissemination and implementation of quality measures for gastrointestinal endoscopy: European Society of Gastrointestinal Endoscopy (ESGE) and United European Gastroenterology (UEG) position statement. Issue 1 (10th February 2021) - Bisschops, Raf; Rutter, Matthew D; Areia, Miguel; Cristiano Spada,; Domagk, Dirk; Kaminski, Michel F; Veitch, Andrew; Khanoussi, Wafaa; Gralnek, Ian M; Hassan, Cesare; Messmann, Helmut; Ponchon, Thierry; et al.
Abstract: The European Society of Gastrointestinal Endoscopy (ESGE) has developed performance measures and established a framework for quality assessment for gastrointestinal endoscopy in Europe. Most national societies actively undertake initiatives to implement and explicitly endorse these quality indicators. Given this, the ESGE proposes that, at a national level, strong leadership should exist to disseminate and implement quality parameters. Thus, understanding the potential barriers that may vary locally is of paramount importance. The ESGE suggests that each national society should prioritise quality and standards of care in gastrointestinal endoscopy in their activities and should survey/understand which measures area local priority to their members and make measuring quality intrinsic to daily endoscopy practice.